Peran Promosi Media Sosial Terhadap Peningkatan Penjualan: Pisang Nyapnyap Karawang - Yulianingsih, Silvi; Retnosary, Rieke; Yani, Dini (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This research on the Pisang Nyapnyap business aims to identify and analyse the most effective forms of social media promotion for reaching customers, increasing sales, and expanding the market for banana-based culinary products. Social media has become one of the most crucial marketing tools for modern businesses to broaden their market reach and enchance customer engagement. Platform such as Instagram, Facebook, and WhatsApp have emerged as essential chsnnels for entrepreneurs to extend their marketing outreach, strengthen customer relationships, and raise brand awareness. This case study employs a qualitative descriptive method, focusing on the Pisang Nyapnyap business located in Kalangsari Village, Rengasdengklok Sub-district, Karawang Regency, West Java. Data were collected through interviews, observations, and analysis of the social media content utilised by the business. The findings reveral that the implementation of social media promotion via Instagram and WhatsApp has significantly boosted sales volume and widened the market reach, positively contributing to the growth of the Pisang Nyapnyap bussiness. The social media promotion strategy, creative content, and responsiveness to market demands have proven effective in maintaining business growth, increasing sales, attracting a broader customer base, and enchaning customer loyalty through innovative product variations and strategic promotions. Consistency in promotional efforts remains esseential to sustaining and improving sales performance. Furthermore, utilising analytical tools provided by platforms such as Instagram Insights in vital for evaluating promotional effectiveness and guiding future marketing strategies.